Losartan Treatment Could Improve the Outcome of TBI Mice - Xiong, Jianhua; Gao, Yalong; Li, Xiaotian; Li, Kai; Li, Qifeng; Shen, Jun; Han, Zhenying; Zhang, Jianning (Frontiers in Neurology, 2020)
Traumatic brain injury frequently leads to serious mortality and physical disability, yet effective treatments remains insufficient. TBI always leads to a series of secondary brain injuries including neuronal apoptosis, continuous inflammation, endoplasmic reticulum stress, and disruption of the blood-brain barrier. Sartans that block angiotensin II type 1 receptors are strongly neuroprotective, neurorestorative and anti-inflammatory. However, whether losartan, a FDA-approved and widely used drug for regulating blood pressure, is beneficial for improving the prognosis of TBI need more evidence. Through a controlled cortical impact injury mice model, we confirmed that losartan treatmeng could ameliorate CCI-induced secondary brain injuriy. We found that losartan treatment decreased brain lesion volume, neuronal apoptosis and ER stress protein ATF4 and eIF2α. Moreover, our results showed that losartan also improved neurological and motor function. It is worth pointing out that losartan increased the expression of tight junction proteins ZO-1 and alleviated brain edema and blood brain barrier leakage. Additionally, losartan inhibited pro-inflammatory factor TNF-α and improve anti-inflammatory factor IL-10. Taken together, our data demonstrated that losartan could improve the prognosis of TBI and may be a promising therapeutic method for mitigating TBI.